Assessment of Bacillus species capacity to protect Nile tilapia from A. hydrophila infection and improve growth performance - Macias, Leslye; Mercado, Víctor; Olmos, Jorge (Frontiers in Cellular and Infection Microbiology, 2024)
Present study evaluated three Bacillus species capacity to improve health status and growth performance of Nile Tilapia fed with high levels of soybean meal and challenged with Aeromonas hydrophila. In vitro experiments showed β-hemolysin and metalloprotease enzymes were produced by A. hydrophila throughout exponential growth phase. In vivo experiments showed that 10 7 CFU/mL of this pathogen killed 50% control group fishes in 13 days. To evaluate Bacillus strains influence on health status and growth performance in Nile Tilapia, 180 fishes (33.44 + 0.05 g) were distributed in 12 tanks of 200 L each and animals were fed twice per day until satiety. 1) Control group without Bacillus, 2) Bacillus sp1, 3) Bacillus sp2 and 4) Bacillus sp3 groups were formulated containing 10 6 CFU/gr. After 40 days of feeding fishes were intraperitoneally injected with one mL of A. hydrophila at 2 x 10 7 CFU/mL and mortality was recorded. Results showed that cumulative mortality rate was significantly (p < 0.05) lower in Bacillus sp1 (25%), Bacillus sp2 (5%) and Bacillus sp3 group (15%), than control group (50%). Weight gained was also significantly better (p < 0.05) in Bacillus sp1 (36%), sp2 (67%) and sp3 group (55%), with respect to control group (30%). In conclusion, functional diet formulated with high levels of soybean meal and supplemented with Bacillus sp2 could be an alternative to protect Nile tilapia cultures from A. hydrophila infections and to improve fish growth performance.